2018
DOI: 10.31083/j.jmcm.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of appropriate housekeeping genes for quantitative RT-PCR analysis in MDA-MB-231 and NCI-H460 human cancer cell lines under hypoxia and serum deprivation

Abstract: Gene expression studies aimed at analyzing cancer cells under hypoxia and serum deprivation conditions show major potential for understanding molecular mechanisms associated with tumor progression as well as resistance to antitumor agents. To the best of our knowledge, a study for the identification of appropriate housekeeping genes in breast and lung cancer cells under hypoxia and serum deprivation conditions is currently missing. Given the relevance of a reliable and accurate normalization, we herein aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…PPIA along with ACTB was found to be the most stable reference gene for basal type breast cancer cell lines in hypoxic and serum deprived conditions [36]. However, our analysis revealed that the expression of PPIA was moderately stable and ranked ninth in the combined analysis (Supplementary File S3).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…PPIA along with ACTB was found to be the most stable reference gene for basal type breast cancer cell lines in hypoxic and serum deprived conditions [36]. However, our analysis revealed that the expression of PPIA was moderately stable and ranked ninth in the combined analysis (Supplementary File S3).…”
Section: Discussionmentioning
confidence: 80%
“…In total, thirteen reference genes were selected by searching for relevant literature related to various breast cancer cell lines [26][27][28][29][30][31][32][33][34][35][36][37][38]. Twelve more genes were selected from the TCGA dataset analysis and were referred to as Novel Candidate Reference genes.…”
Section: Selection Of Reference Genes and Primer Designmentioning
confidence: 99%
See 3 more Smart Citations